2023
DOI: 10.1039/d3ta02128a
|View full text |Cite
|
Sign up to set email alerts
|

High ionic conducting rare-earth silicate electrolytes for sodium metal batteries

Abstract: Sodium gadolinium silicate solid electrolyte showed an outstanding sodium plating/stripping performance for 1000 cycles that proves excellent interfacial contact between the sodium anode and solid electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Shannon et al were the first to report the ionic conductivity and determine the true crystal structure of these compounds . These phases generated a lot of interest recently. Shannon et al prepared a series of compounds by substituting M with various elements (M = Fe, Sc, Y, and rare earth Lu–Sm). They found that the ionic conductivity increased linearly with the ionic radii of the M 3+ ion in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Shannon et al were the first to report the ionic conductivity and determine the true crystal structure of these compounds . These phases generated a lot of interest recently. Shannon et al prepared a series of compounds by substituting M with various elements (M = Fe, Sc, Y, and rare earth Lu–Sm). They found that the ionic conductivity increased linearly with the ionic radii of the M 3+ ion in the structure.…”
Section: Introductionmentioning
confidence: 99%